Understanding Government Budgets A Practical Guide. - Musell, R. Mark.; Yeung, Ryan, 1982- (Milton : Routledge, 2019)
Public budgets follow rules of presentation and use terms that make sense to few outside the world of public finance. Moreover, practices vary widely among the thousands of governments across the globe, between federal, state, and local levels of government in the United States, and among nonprofit organizations, many of which provide services similar to governments. Understanding Government Budgets, Second Edition offers a detailed examination of each of the different types of information found in budgets, featuring annotated examples from a variety of organizations. It expands on explanations in the previous edition by including a wealth of examples from governments abroad and from the nonprofit sector. The book stresses that the choices made about content, format, and organization influence the story a budget tells. Designed to help citizens, students, and policy makers become more informed users of public budgets, this book makes the format of budgets and the information they contain accessible and understandable, providing users with the tools they need to make better sense of public organizations and their performance. Perfect for undergraduate or graduate-level courses in budgeting and public administration, Understanding Government Budgets, Second Edition also offers a useful guide to budgets for the average citizen with an interest in how government operates.
11 Budgeting in Nonprofits: Examples from Labor, Research, Arts, and EducationNotes; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Budget -- United States; Government spending policy -- United States; United States -- Appropriations and expenditures; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development